2011
DOI: 10.3171/2011.6.jns11513
|View full text |Cite
|
Sign up to set email alerts
|

Genu of corpus callosum as a prognostic factor in diffuse axonal injury

Abstract: Regardless of the number of lesions, the existence of a genu lesion suggested disability 1 year after TBI in patients with DAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…Primary direct contusion likely was a major factor in the evolution of the hematoma in the CC, as penetrating cortical medullary arteries in the CC have their major sweep in the coronal plane and may be vulnerable to shear and stress due to impact along the long axis of the skull. 18) In addition, hemorrhage of the interhemispheric fissure cistern along with the hematoma was found in both of our cases, and this was also found in other studies; 3,19) this may be associated with the delayed hematoma of the CC. Although traumatic intracranial aneurysm is one of the causes of delayed apoplexy in patients with severe head trauma 20) following direct mural injury or acceleration-induced shearing force, 21) neither of our cases showed this vascular abnormality through CTA and/or DSA.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Primary direct contusion likely was a major factor in the evolution of the hematoma in the CC, as penetrating cortical medullary arteries in the CC have their major sweep in the coronal plane and may be vulnerable to shear and stress due to impact along the long axis of the skull. 18) In addition, hemorrhage of the interhemispheric fissure cistern along with the hematoma was found in both of our cases, and this was also found in other studies; 3,19) this may be associated with the delayed hematoma of the CC. Although traumatic intracranial aneurysm is one of the causes of delayed apoplexy in patients with severe head trauma 20) following direct mural injury or acceleration-induced shearing force, 21) neither of our cases showed this vascular abnormality through CTA and/or DSA.…”
Section: Discussionsupporting
confidence: 89%
“…4,19),32) Poor outcome is associated with increasing age, low admission GCS, and the presence of space-occupying lesions, 33,34) especially those that involve both the genu and the splenium. 3) In our case 2, the patient’s GCS level was 15 upon admission, and he experienced immediate onset of coma and underwent emergency surgery. In case 2, a relatively low ICP was observed postoperatively until the patient died.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…3,11) In this study, there were no differences in outcome according to the location of microbleeds. However, the small number of patients with microbleeds in the corpus callosum and the brainstem limits this comparison, and more patients are needed to address this point.…”
Section: Discussionmentioning
confidence: 65%
“…In this patient, the correlation between the lesion and neurological outcome was not clear, because he had already shown delayed development before the accident. Matsukawa et al 6 reported that the presence of a callosal genu lesion suggests disability 1 year after TBI in patients with diffuse axonal injury. In our patient, developmental delay was mild almost equally before and after TBI.…”
Section: Discussionmentioning
confidence: 99%